A suspected virus infection of the oral mucosa in Swedish reindeer (Rangifer tarandus L) - Rehbinder, C.; Nordkvist, M.; Moreno, J. W.; Siddiqui, Islam-Ud-Din (Rangifer, 1986)
In 1980 a rather high frequency of reindeer, supplementarily fed in pens, were taken ill and deaths occurred as well. In five out of eight carcasses necrophsied oral lesions were observed. Histologically the mucosa, surrounding these lesions, was charasterized by the presence of intracytoplasmic inclusion bodies, inter- and intracellular oedema and vesicle formation. Fusobacterium necrophorum, Coll, betahaemolizing streptococci, and Cory neb acterium pyogenes found in the lesions were all considered secondary invaders. Serological samples from disease stricken herds were tested for antibodies against BVD-, P13-, and IBR-virus as well as Chlamydia. Low positive titres were observed but for BVDV. The result indicates that a thus far unidentified virus might be the primary cause of this enzootically occurring disease.